A new type of cuprous-cysteamine sensitizers: Synthesis, optical properties and potential applications. (July 2021) - Wang, Y.; Alkhaldi, N.D.; Pandey, N.K.; Chudal, L.; Wang, L.Y.; Lin, L.W.; Zhang, M.B.; Yong, Y.X.; Amador, E.H.; Huda, M.N.; Chen, W.
Abstract: Herein, for the first time, we report a series of cuprous-cysteamine (Cu-Cy-X, X = F, Cl, Br, and I)) sensitizers that possess tunable fluorescence from orange to yellow. The Cu-Cy-X can generate reactive oxygen species (ROS), including singlet oxygen ( 1 O2 ) in the order of Cu-Cy-I > Cu-Cy-Br > Cu-Cy-Cl ≈ Cu-Cy-F under UV and microwave excitation. Further study revealed that Cu-Cy-X has stability in the order of Cu-Cy-I > Cu-Cy-Br > Cu-Cy-Cl ≈ Cu-Cy-F. In this work, a detailed synthesis technique, crystal structure, optical properties, and mechanism of the observed trend in 1 O2 generation, luminescence spectra, and anticancer effect are discussed in both theoretical and experimental points of view. These new materials will open a new door for photodynamic therapy and many other potential applications such as sensing, lighting, displays, labeling, and medical imaging. Graphical abstract: Image 1 Highlights: a series of new cuprous-cysteamine (Cu-Cy-X, X = F, Cl, Br, and I)) sensitizers were reported. Cu-Cy-X possess tunable fluorescence from orange to yellow. Cu-Cy-X can generate reactive oxygen species in the order of Cu-Cy-I > Cu-Cy-Br > Cu-Cy-Cl ≈ Cu-Cy-F. Cu-Cy-X has stability in the order of Cu-Cy-I > Cu-Cy-Br > Cu-Cy-Cl ≈ Cu-Cy-F. These new sensitizers open a new door for photodynamic therapy and have many other potential applications.